Phenomenon the Day of Week and Monday Effect on the Return of The Jakarta Composite Index (JCI) - Assyifa, Baiq Siti Ainaya; Hascaryani, Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
There is enough information to influence price movements in the capital market. Investors often overreact to this information, significantly affecting their investment decisions and potentially triggering market anomalies. This study aims to analyze the day of the week effect and Monday effect anomaly on the return of the Jakarta Composite Index (JCI) at the Indonesia Stock Exchange during the period 2019-2023, using closing price data. The research employs descriptive and quantitative methods, using non-parametric statistical tests, Kruskal-Wallis and Mann-Whitney U Tests, to analyze differences in daily stock returns. The results indicate significant differences in the average stock returns across the five trading days, suggesting the presence of the day of the week effect. Additionally, it was found that returns on Monday tend to be lower and negative, supporting the existence of the monday effect. These findings suggest a violation of the weak-form efficient market hypothesis, where returns should not be predictable based on specific days. The practical implications of this study can assist investors in designing investment strategies.